Website-Based Learning Media on Reading and Numeracy Content for Third Grade Elementary Schools - Arifin, Yuli Fajar; Nugroho, Yusuf Sulistyo (International Journal of Elementary Education, 2023)
Learning technology continues to improve along with the times. The role of technology currently has very rapid development in various fields. Many media can help improve the quality and quantity of learning, one of which is the application of website-based learning. This study aims to develop web-based learning media on reading and arithmetic content for third-grade elementary school students and test the feasibility of these learning media. This study used the R&D (Research and Development) development method with the Luther Sutopo version of the MDLC development model. The method used to collect data is suryev. The instrument used to collect data is a questionnaire. The research subjects were two learning media experts and two learning material experts. The data analysis technique used is quantitative. The research results, namely the assessment given by learning media experts, have an average value of coefficient V 0.87, declared valid. The material expert validator has an average efficiency value of V 0.81, declared valid. The average result of a user questionnaire, namely grade III elementary school students, is 83.12 in the excellent category. Based on the results of tests, Web-based learning media on reading and arithmetic content for grade III elementary school students is feasible.